Shear strength of oil palm shell foamed concrete beams - Jumaat, Mohd Zamin; Alengaram, Ubagaram Johnson; Mahmud, Hilmi (Elsevier, 2009)
Four reinforced oil palm shell foamed concrete (OPSFC) beams were fabricated, and their shear behaviour was tested. The OPSFC has a target density of approximately 1600 kg/m(3) and a 28-day compressive strength of about 20 MPa. Two beams were cast with shear reinforcements while the other two were cast without such reinforcements. For comparison, four reinforced normal weight concrete (NWC) beams were also cast. The beams that contained shear links failed in flexure mode, while those without links failed in shear mode. The experimental results indicated that the shear capacities of OPSFC beams without shear links are higher than those of the NWC beams and exhibit more flexural and shear cracks.